The Determinant of Indonesia Enterpreneur’s Intention to Pay Zakat: Does Government Support Matter? - Akhsyim Afandi; Heri Sudarsono; Rindang Nuri Isnaini Nugrohowati; Yunice Karina Tumewang (Global Review of Islamic Economics and Business, 2022)
This study aims to analyze the entrepreneur’s behavior to pay zakat and to formulate the role of zakat institutions such as the National Zakat Board (BAZNAS) and Amil Zakat Institution (LAZ) in improving total zakat collection. Total respondents in this research are 751 entrepreneurs across 28 provinces in Indonesia. Partial least squares structural equation modeling (PLS-SEM) was used to know the entrepreneur’s behavior in paying zakat. Attitude toward moral reasoning, influence of religious leaders, peer influence, zakat knowledge, zakat system structure, enforcement of zakat law, and government support affect the interest of entrepreneurs to pay zakat. However, the attitude toward zakat evasion and transparency of zakat management does not affect the interest of entrepreneurs to pay zakat. The role of the government is getting a spotlight in this study because of its significance in formulating relevant policies to increase the interest of entrepreneurs to pay zakat. The establishment and supervision of zakat institutions as well as the issuance of supportive regulation is considered important in this study.